Small Business Still Missing the Boat on Social Media and Internet Advertising - Sullivan, Daniel; Fox , Dan; Stoll , Robert; Jacobs , Raymond (Journal of Marketing Development and Competitiveness, 2021)
The United States economy is heavily dependent on the success of its 30.2 million small businesses. These businesses typically operate in local markets. Constrained by the limitations of local markets, many small business owners struggle daily to keep their businesses afloat. The pressure of maintaining and operating a small business leaves little time for advertising. In an age of digital media and online retailing, many small businesses still fail to embrace the internet and social media as platforms for growing their firms and increasing their customer base. This study examines the reasons small business fail to embrace digital media and continue to hold onto traditional business models.